A Case of Rash with Flagellate Erythema and Muscle Weakness: Another Example of Dermatomyositis - Rita Reis Correia; Paulina Mariano; Sandra Martin; Maria Eugenia André (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
.